Perbandingan Nilai Kuat Tekan Beton Menggunakan Hammer Test dan Compression Testing Machine terhadap Beton Pasca Bakar - Dharmawan, Weka Indra; Oktarina, Devi; Safitri, Mariana (MEDIA KOMUNIKASI TEKNIK SIPIL, 2016)
The change of temperature is quite high, as was the case in the event of a fire, it will have an impact on the concrete structure. Because in the process there will be a cycle of alternately heating and cooling, which would lead to a change in phase of the complex physical and chemical basis. Using hammer test as a comparison of compression testing machine (CTM) in normal conditions the concrete now widely used and has had standardization. The objects to test consist of 60 concrete cubes beam of 15 cm x 15 cm x 15 cm which burned for 3 hours with 3 variants of temperatures. The 20 samples used as a blank test and each 20 samples burnt with temperature 300oC and 600oC. The results showed the increase in the compressive strength at the temperature of 300oC in the amount of 6.68% or 10.91 Kg/cm2, and at the temperature of 600oC has decreased by 1.57% or 2.56 Kg/cm2 on hammer test. While the testing with compression strength of concrete decreased at temperatures of 300oC and 600oC respectively is 15.77% or 51.1 Kg/cm2 and 21.89% or 70.93 Kg/cm2.